Análisis comparativo de la Presentación personal virtual en diferentes espacios de interacción. - Carlos ARCILA CALDERÓN (Fonseca: Journal of Communication, 2014)
This paper examines the presentation of a group of individuals in different virtual environments. The objective is to compare the communication of identity in each space and in different times, and to describe the effort held to each identity category, in order to know if the masks used by these individuals were the same (repeat) or changes (contradiction).To do this, we made a comparative analysis between several presentations in virtual environments (chat, blog and social network) and physical spaces (an identity questionnaire), that 14 individuals made for a former research. According to the findings, the most significant communicative effort to produce identity was employed in Chats. Additionally, we saw that the biggest number of masks was elaborated “independently”, it means that individuals use multiple identities elements to talk about themselves. Most masks were constant (like age, name and place of residence), and just a few changed or were obviously contradictories.